Application Design The Data Collection Features of The Hotel Shades of Rantauprapat Using VBNET - Syaiful Zuhri Harahap; Samsir (Publisher Cv. Inara, 2020)
Hotel reservation is an activity where a customer comes to the hotel to book a room and stay in a room that has been booked. Orders are made by customers, at the hotel Shades Rantaupapat the process of collecting the customers who will stay is still done manually. So that customers have to come to the hotel to make reservations directly. This reservation information system is an application that can help speed up registration or registration when at the reception. Cancellation can also be directly managed by the admin or receptionist. So as to provide other convenience in making reservations. In making this information system using a system development method in the form of a waterfall. At the time of making the programs using Visual Basic NET 2010. For databases that are used to create databases using SQL Server 2008. The application of this information system can help employees to record customers who stay overnight and manage information needs needed to support the hotel business.